Analysing smart power grid against different cyber attacks on SCADA system. (10th June 2021) - Akhtar, Tafseer; Gupta, B.B.
The integration of information and communications technology (ICT) with traditional power grid is transforming the power grid into a more reliable and smarter cyber physical system (CPS). A supervisory control and data acquisition (SCADA) system is used to implement the cyber layer for power grid, which is responsible for real-time monitoring and control of power grid and power delivery network. A SCADA system combined with other devices creates smart power grid environment, but it also makes power grid vulnerable against different cyber-attacks as it requires connection with various kinds of open networks. Smart power grids are a extremely critical infrastructure and attack of any kind can affect socio-economical condition of the region. In this paper we present a non-complex co-simulation environment for analysing smart power grid using OMNeT++ and openDSS, which also includes two different cyber-attack scenarios. The main contribution of the paper lies in the behavioural analysis of the smart power grid environment while various attacks are performed on cyber layer of the grid and respective response of the power grid during these attacks. The findings of the proposed work show the vulnerabilities of smart power grid, as during cyber-attacks power grid was unstable and power generation was dropped significantly.